2013
DOI: 10.1111/jpy.12091
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach for the development of axenic microalgal cultures from environmental samples

Abstract: We demonstrated a comprehensive approach for development of axenic cultures of microalgae from environmental samples. A combination of ultrasonication, fluorescence-activated cell sorting (FACS), and micropicking was used to isolate axenic cultures of Chlorella vulgaris Beyerinck (Beijerinck) and Chlorella sorokiniana Shihira & R.W. Krauss from swine wastewater, and Scenedesmus sp. YC001 from an open pond. Ultrasonication dispersed microorganisms attached to microalgae and reduced the bacterial population by 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…All dominant, cultivable, unialgal strains from HRAP were isolated using micropicking followed by continuous serial dilutions 18 . Further morphological analysis followed by phylogenetic analysis of the unialgal strains revealed that these strains were Pediastrum sp., Parachlorella sp., Dictyosphaerium sp., Desmodesmus sp., and Scenedesmus sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All dominant, cultivable, unialgal strains from HRAP were isolated using micropicking followed by continuous serial dilutions 18 . Further morphological analysis followed by phylogenetic analysis of the unialgal strains revealed that these strains were Pediastrum sp., Parachlorella sp., Dictyosphaerium sp., Desmodesmus sp., and Scenedesmus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, all cultures were grown in BG11 agar plates and liquid medium in triplicates with a continuous illumination at a light intensity of 130 µmol·m −2 ·s −1 and temperature of 25 °C for seven days. Isolated prokaryotic and eukaryotic strains were identified by sequencing 16S rRNA gene and 18S rRNA gene, respectively 18 . The details of the primer sets are described in the succeeding section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Cho et al. ), one reason for this being the generally low level of recovery of viable cultures after sorting.…”
mentioning
confidence: 99%
“…Flow cytometry sorting has been successfully applied to recover natural populations for genetic and genomic characterization (Shi et al 2009, Woyke et al 2009, Rinke et al 2013, as well as for physiological measurements such as their capacity to fix carbon (Jardillier et al 2010). However, this technique has relatively rarely been used to bring novel microorganisms into culture (Sensen et al 1993, Sieracki et al 2005, Sinigalliano et al 2010, Cho et al 2013), one reason for this being the generally low level of recovery of viable cultures after sorting.…”
mentioning
confidence: 99%